Analisis Kualitas Kelayakan Buku Tematik Terpadu Kurikulum 2013 Di Semester Genap Kelas III Sekolah Dasar - Nahdia Rahman, Tiara Hilwia; Iswara, Prana Dwija; Karlina, Dety Amelia (Jurnal Pena Ilmiah, 2021)
Teaching materials or textbooks have a significant role in a learning activity. This study focuses on integrated thematic books for class III by used qualitative descriptive methods to describe the quality of content feasibility and language feasibility of integrated thematic books in third-grade elementary schools. The study results : (1) aspects of material suitability with KI/KD for both books are contains in the appropriate category; (2) the accuracy aspect of the 6-theme book material is included in the less feasible category, while the accuracy of the 7-theme book material is contained a very appropriate category; (3) aspects of learning support materials for the two books are in the very appropriate category; (4) the communicative aspect, the aspect of conformity to the level of student development and the aspect of coherence and unity of ideas in the two books are included in the very feasible category.